STUDENTS’ PERCEPTION ABOUT IMPROVING ENGLISH LISTENING SKILLS USING MOVIES AMONG THE VOCATIONAL HIGH SCHOOL STUDENTS - Pamungkas, Irvan Bagus Aji; Adi, Sugeng Susilo (Erudio Journal of Educational Innovation, 2020)
Nowadays, teaching media is developed well in many kinds especially for English listening skill. Listening is the first communication skill human acquired. It is an important process which has vital role in the daily activity. The example of teaching media to be used in listening class is English Movie. The researcher conducted watching English movie activity in the class and he realize that the teaching media is interesting to be used because students are easy to get bored when they have listening activity without visual media. Then, he wants to know the students’ perception about the use of English movie. This study aims to know students’ perception about the use of English movie to improve listening skill in SMKN 10 Malang. The subject of this study are eleventh grade students of SMK Negeri 10 Malang 2019/2020. The researcher takes 100 participants. The method of the study was survey with qualitative desciptive. The data was collected from online questionnaire answered by the students. The researcher used online questionnaire through Google Form to ease him in collecting and analyzing the data. The result of this study showed that students have positive responses on using English movie that they believe that using English movie can increase their listening skill. The students of eleventh grade at SMKN 10 Malang support this idea and agreed that English movie is a profitable tool as a listening media. It can be concluded that students’ perception about the use of English movie to improve listening skill is positive.